PENGARUH LABA DAN ARUS KAS TERHADAP NILAI PASAR SAHAM BERDASARKAN SIKLUS HIDUP PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ima Andriyani (KOLEGIAL, 2013)
This study was conducted to examine the effect of profit and cash flow to stock market value based on lifecycle of manufacturing companies in Indonesian Stock Exchange.The population of this study was 254 issuers running on manufacturing sectors. The issuers were registered in the Indonesian Stock Exchange as listed in the Indonesian Capital Market Directory from the year 2004 up to 2011. Twenty three out of 254 issuers were taken as sample. The sample taking was taken based on the indicators of sales growth ranking, dividend payment, profit/loss, and liquidity level. The sample size was calculated using quartile system of company’s lifecycle. The lifecycle of a company was divided into three stages: start-up, growth, mature, and decline. The secondary data recorded in the Indonesian Stock Exchange was used in this study. The observed objects were company financial reports from December 31, 2004 up to December 31, 2011. Modified Multiple Liner Regression Model was used to meet the assumptions of its multivariate linear model. There were four findings found from the study. First, on start-up stage, the value of company’s stock market was influenced by investment cash flow and financing cash flow. However, profit and investment cash flow had no correlation to stock market value. Second, on growth stage, the value of company’s stock market was influenced by profit, operating cash flow, and financing cash flow. On the other hand, investment cash flow had no correlation to stock market value. Third, on mature stage, stock market value was influenced by profit, operating cash flow, investment cash flow, and financing cash flow. Fourth, on the decline stage, stock market value was influenced by operating cash flow and financing cash flow. However, profit and investment cash flow had no correlation to stock market value.